Toksisitas Produk Ekstrasellular (ECP) Streptococcus agalactiae pada Ikan Nila (Oreochromis niloticus) - Hardi, Esti Handayani; Sukenda, Sukenda; Harris, Enang; Lusiastuti, Angela Mariana (Jurnal Natur Indonesia, 2011)
This research aimed to know the toxicity of extracellular products (ECP) of Streptococcus agalactiae was tastedin cultured Nile tilapia (Oreochromis niloticus). Streptococcus agalactiae had two haemolytic types: β-haemolyticand non-haemolytic type. Toxicity test of ECP to know the virulancy factor of S. agalactiae was still limited. It wasfound that after tested on 15 fish weighing 15 g through intraperitoneal injection 0,1 ml/fish, both bacteria causedchanges in swimming pattern, palatability, external and internal anatomy macroscopically and microscopically.Extracellular products of S. agalactiae non-haemolytic type (BHIA and BHI 24 h) and β-haemolytic type (BHI 72 h)caused mortality 12 hours after injection and the mortality continued till day 7 th of culture. Whirling happened 96hours after injection with ECP S. agalactiae β-haemolytic type (BHIA 72 h incubation) whereas injection with ECP(BHI 24 h) on 72 h after injection and continued untill day 7 th. Behavior disease signs caused by S. agalactiaeoccured on eyes. There were opacity, purulens, eye shrink, lateral and bilateral exopthalmia and haemorrhage oninfected-fish. Silver staining of sodium dodecyl sulphate-polyacrylamide gels to S. agalactiae revealed thatpredominant 51.8-69.6 kDa bands were present in BHIA ECP fraction. The 69.6 kDa was absent from the BHI ECP.Total protein on non-haemolytic S. agalactiae ECP are 28.18 ppm on BHIA medium and 13.64 ppm on BHI medium.Whereas β-haemolytic S. agalactiae ECP are 2.73 ppm on BHIA medium and 8.18 ppm on BHI medium. Concentrationof protein in ECP was one of factor that caused non-haemolytic S. agalactiae more virulent than β-haemolytic type.The conclusion from the research that ECP was virulent factor on β-haemolytic and non-haemolytic S. agalactiaein fish which caused changes in behavior disease signs.